Процеси капіталізації корпорацій та їх відображення у звітності - Яремко, І. Й.; Лемішовська, О. С.; Yaremko, I.; Lemishovska, O. (Видавництво Львівської політехніки, 2017)
Розглянуто зміст вартісних критеріїв в управлінні процесами капіталізації корпорацій, зміст формалізованих у фінансовій звітності показників, їхню вартісну спрямованість та розкрито характеристику показників й індикаторів у системах і моделях створеної вартості підприємством. Окреслено можливості інтеграції інстру- ментарію вимірювання вартісних параметрів і традиційних показників фінансової (корпоративної) звітності.

The content of cost criteria in managing the processes of capitalization of corporations, the content of the formalized financial statements of indicators, their value orientation and the disclosure of characteristics of indicators and indicators in the systems and models of the created value of the enterprise are considered. The possibilities of integration of tools for measuring cost parameters and traditional indicators of financial (corporate) reporting are outlined. The content of capitalization of enterprises of corporate type, which in the developed markets of capital and investments is considered through the growth of the market value of equity capital of an economic entity, is disclosed. The main problems are analyzed which make it impossible to use the economic tools developed for the companies of the developed economies in the national practice of capitalization of corporations management. The critical analysis of the ability of indicators of public financial (corporate) reporting to objectively characterize the capitalization of Ukrainian corporations that are not quoted on stock exchanges is investigated and conducted, and serve as a reliable information and analytical base for the purpose of managing their capitalization. Some directions of perfection of the structure and format of corporate reporting for its adaptation to the needs of valueoriented management, increase of efficiency of processes of capitalization of Ukrainian corporations are offered. The content of the index of economic added value is researched, its interrelation with the indicator of accounting profit, reflected in corporate reporting, its informative ability to characterize the growth of own capital of the companies is shown. The expediency of using the modified indicator of economically added value in the system of managing capitalization processes in the domestic practice is substantiated. In order to substantiate the feasibility and justification of the use of the economically added value indicator, the main variants of measurements of results in the models of cost effectiveness estimation were analyzed and the key criteria in these models were compared with the formal indicators of public financial reporting of enterprises of corporate type.
Processes of capitalization of corporations and their replacement
Keywords: корпорація; показники; індикатори; критерії; фактори капіта- лізації; системи і моделі вартісного виміру; фінансова звітність; показники прибутковості; corporation; indicators; indicators; criteria; capitalization factors; systems and models of cost measurement; financial reporting; profitability indicators; 658.012